THE APPLICATION OF ISLAMIC BUSINESS CONTRACT IN THE NATIONAL LAW REGULATIONS (THE COMPARISON BETWEEN COUNTRIES WITH CIVIL LAW SYSTEMS AND COMMON LAW SYSTEMS) - Dewi, Gemala (UI Scholars Hub, 2021)
With the growth of Islamic banking and finance business in many countries nowadays, the legal aspect is very important to be understood by the parties. This is because in Islamic business law, not only the contract becomes law for the parties, but also to be compliant with Islamic teachings. Otherwise it will be null and void that could cause loss to both sides. However, in some Civil Law system countries there might not be clear rules regarding Islamic contract law. Also, in Common Law system countries, with the character of Islamic law which has specific provisions on the law of contracts needs to comply with the rules in practical Islamic business. In addition, the function of the court in finding the law for dispute settlement in Islamic business transactions becomes a necessity. For this reason, it is important to see how are the countries with the Civil Law and the countries with the Common law system applying Islamic business contract law. In This paper will be compared the application of Islamic business contracts in the national law regulations of two countries, Indonesia (with Civil Law System) and Malaysia (with Common Law system). The main focus of this research is the application of transactions based on sharia principles on the regulations and the legal process by the law enforcers in the compared countries based on their different legal system. The result to be expect is to find the similarities and the differences amongst the two countries.